Pros and cons being a part-time music teacher among music students in Universiti Teknologi MARA (UiTM) / Nur Shafreeza Zainal Abidin - Zainal Abidin, Nur Shafreeza (Faculty of Music, 2016)
The main aim of this thesis is to study the pro and cons being a part-time music teacher amongst music's students in Universiti Teknologi Mara (UiTM). The paperwork includes information of part-time jobs, the effects for music students who doing part-time job, and how the students perceive their capability to teach part-time. This study is performed to measure the advantages and challenges by being a music teacher while still studying in Faculty of Music, Universiti Teknologi Mara. To achieve this, data has been collected by research from questionnaires from other researchers, books, online journal and peer's self-thoughts. The paper analyzes the overall factor that happened before, during teaching experiences and future social possibilities in this career. Through researcher's own experiences during three-year studies for Bachelor's Degree in UiTM, the researcher has involved in teaching music career. Most of the time, the career has been done by herself. In researcher's own hypothesis, some of music students are afraid to involve in teaching career as part-time job; lack of teaching skills and ability to sight read and facing low self-confidence to work with new environment and new people. Thus, using all the information received, the researcher will design interview questions based on the issues related to the topic.